A modifying respiratory muscle device: development and pilot testing - Chanavirut, Raoyrin; Yensano, Rattakarn; Yonglitthipagon, Ponlapat; Nakmareong, Saowanee; Chaipattaranun, Lapasrada; Jaratpongtakul, Warisara (Journal of Associated Medical Sciences, 2025)
Background: A respiratory muscle device was designed in various forms and was available at different price ranging. However, financially disadvantaged users may find it difficult to afford the device. Objectives: The objective of the study was to develop a device utilizing readily available materials. Subsequently, a pilot study was conducted to evaluate maximal inspiratory pressure (MIP) among healthy adult subjects. Furthermore, feedback and suggestions regarding the device were collected using a questionnaire. Materials and methods: The device’s components were evaluated to ensure safety. Subsequently, laboratory tests were conducted to assess device performance, including measurements of windmill blade rotation and airflow, to determine and prescribe the exercise intensity. Healthy subjects aged 18 to 25 years were then recruited and randomly assigned into either the control group or the exercise group (N=16 per group). Subjects in the exercise group were instructed to use the device daily for four weeks, while those in the control group were asked to continue their usual daily activities. MIP was measured in all participants on a weekly basis throughout the study. Then, subjects in the exercise group were given a questionnaire to evaluate their opinions regarding the device. Results: The result revealed that all components of the device complied with safety standards. There was no significant difference in MIP between the exercise group and the control group. However, by the third and fourth weeks of the training period, the exercise group exhibited a significant improvement in MIP compared to their values in the first week. Furthermore, user feedback indicated that the device’s size, weight, and usability were very satisfactory. Conclusion: The study concluded that the modified device did not have a significant effect on inspiratory muscle strength, as indicated by MIP, in healthy adult subjects. However, further research is warranted to more thoroughly evaluate the effectiveness of the device and in relevant clinical populations.